Prodromal Dementia With Lewy Bodies and Recurrent Panic Attacks as the First Symptom: A Case Report - Jaramillo-Jimenez, Alberto; Ying, Yinbing; Ren, Ping; Xiao, Zhan; Zhang, Qian; Wang, Jian; Rong, Han; Borda, Miguel Germán; Bonanni, Laura; Aarsland, Dag; Wu, Donghui (Frontiers in Neurology, 2022)
Psychiatric-onset dementia with Lewy bodies (DLB) might include symptoms of depression, hallucinations, anxiety, and apathy. Here, we report a patient with DLB with recurrent panic attacks as her first symptom 5 years before a biological-based diagnosis of probable DLB. We provide an extended description of the clinical presentation and course from psychiatric-onset DLB to dementia in an 83-year-old woman. This case illustrates the common misdiagnosis of DLB and the delay of having a detailed clinical and biomarker assessment for structured diagnosis. With a detailed description of the clinical presentation of this case, the empirical treatment strategies, and the patient perspectives, we aim to make clinicians aware of panic attacks within the psychiatric-onset DLB.